Impact of treatment and outcomes for patients with posttransplant drug‐associated thrombotic microangiopathy. Issue 11 (23rd August 2017) - Epperla, Narendranath; Hemauer, Kathleen; Hamadani, Mehdi; Friedman, Kenneth D.; Kreuziger, Lisa Baumann
Abstract : BACKGROUND: Drug‐induced transplant‐associated thrombotic microangiopathy (DTA‐TMA) is a rare but serious complication that can occur after hematopoietic cell transplantation (HCT) or solid organ transplantation (SOT) without guidelines for optimal management of this condition. STUDY DESIGN AND METHODS: Given the ambiguity surrounding the treatment for DTA‐TMA, we conducted a retrospective review to evaluate the impact of different treatment strategies in DTA‐TMA patients. Our primary endpoint was to determine the overall response rate (ORR) for DTA‐TMA based on the type of treatment modality chosen while secondary endpoints included the time to response, relapse rates, and overall survival for DTA‐TMA cases. RESULTS: There were a total of 14 DTA‐TMA patients of whom nine were post‐HCT and five were post‐SOT. Most of the DTA‐TMA cases were due to tacrolimus (n = 11) with a minority related to sirolimus (n = 3). A total of nine of 14 patients demonstrated response and five had no response to therapy. The ORR among the DTA‐TMA patients after HCT and SOT who received plasma exchange (PLEX) were 25 and 100%, respectively. The ORRs among the patients (includes HCT and SOT) who received rituximab (n = 3) and eculizumab (n = 5) were 67 and 60%, respectively. There were two relapses noted in our study and both were in the HCT group. CONCLUSION: While discontinuation of the offending agent may be sufficient for treatment of DTA‐TMA after HCT, PLEX may be a reasonable option for DTA‐TMA after SOT. Although the results are encouraging with rituximab and eculizumab in the treatment of DTA‐TMA, larger prospective studies are needed to validate our findings.